2013
DOI: 10.1186/1471-2180-13-252
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance induced decoupling between host genetics and composition of the associated microbiome

Abstract: BackgroundStudies of oyster microbiomes have revealed that a limited number of microbes, including pathogens, can dominate microbial communities in host tissues such as gills and gut. Much of the bacterial diversity however remains underexplored and unexplained, although environmental conditions and host genetics have been implicated. We used 454 next generation 16S rRNA amplicon sequencing of individually tagged PCR reactions to explore the diversity of bacterial communities in gill tissue of the invasive Pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 57 publications
7
108
1
Order By: Relevance
“…Thus, the lower community stability at 22 1C (Figure 4b) and temperature-or stressrelated increase in potentially pathogenic bacteria (Supplementary File 2) could have contributed to the observed mortality pattern. However, microbiomes often remain stable and pathogen-free even in stressful conditions (Erwin et al, 2012;Simister et al, 2012;Pita et al, 2013;Wegner et al, 2013), indicating their potential role in host acclimation (Rosenberg et al, 2007). Phylogenetic similarity of the microbiomes suggests a common origin from the local seawater microbiota (Lozupone et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the lower community stability at 22 1C (Figure 4b) and temperature-or stressrelated increase in potentially pathogenic bacteria (Supplementary File 2) could have contributed to the observed mortality pattern. However, microbiomes often remain stable and pathogen-free even in stressful conditions (Erwin et al, 2012;Simister et al, 2012;Pita et al, 2013;Wegner et al, 2013), indicating their potential role in host acclimation (Rosenberg et al, 2007). Phylogenetic similarity of the microbiomes suggests a common origin from the local seawater microbiota (Lozupone et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Tissues of healthy marine invertebrates usually harbor species-rich microbial communities (Prieur et al, 1990;Gomez-Gil et al, 1998;Romero et al, 2002;Gomez-Gil et al, 2010;King et al, 2012;Trabal et al, 2012;Wegner et al, 2013). This also applies to the hemolymph (Olafsen et al, 1993;Garnier et al, 2007, Wendling et al, 2014-the functional analog of blood in vertebrates (Bachere et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Vibrio spp. are virtually absent from oyster tissue during winter months [41], and their abundance and diversity increases from spring to summer, reaches a peak during spawning season before decreasing towards autumn [24]. Thus, Pacific oysters do not have a constant Vibrio community but rather take up strains from the local environment making it highly unlikely that the strains used here share a longer coevolutionary history exceeding the time since invasion into the Wadden Sea.…”
Section: (A) Local Adaptation To Vibrio Communities Is Environment Dementioning
confidence: 99%
“…This indicates that the taxonomic composition of strains used here was independent of the invasion source of the host. While oyster associated microbiota can assemble according to host genotype [41], Vibrio spp. in oyster haemolymph are most probably taken up from the environment and vary seasonally with environmental temperature [24,42].…”
Section: (A) Local Adaptation To Vibrio Communities Is Environment Dementioning
confidence: 99%
“…Several recent works (Aravindraja et al 2013;Bartram et al 2014;Bowen et al 2012;Dohrmann et al 2013;Gibbons et al 2013;Kim et al 2013;Logares et al 2013;Oh et al 2013;Portillo et al 2013;SĂĄnchez et al 2013;SzĂ©kely and Langenheder 2014;Wegner et al 2013), mainly performed with nextgeneration sequencing technologies, have demonstrated that most bacterial communities are composed of a few abundant taxa and a plethora of rare ones (PedrĂłs-AliĂł 2012). Such different fractions may have in theory different taxonomic signatures (at the various taxonomic levels), in relation to the physiological features of the groups of taxa present.…”
mentioning
confidence: 99%